Conditional Contracts for the Sale of Land - Sinnadurai, Visu (Journal of Malaysian and Comparative Law, 2019)
It is not uncommon for parties to enter into agreement for the sale and purchase of land subject to certain conditions being fulfilled. Parties may agree that the contract is made "subject to contract"; "subject to approval by some authority"; "subject to the purchaser obtaining a loan" or such other similar terms.